2008
DOI: 10.1109/led.2008.2002946
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Migration-Induced Interface Dipole Effect in n-Doped GaAs/AlGaAs Terahertz Detectors

Abstract: Abstract-A heterojunction interfacial workfunction internal photoemission (HEIWIP) terahertz detector with ∼1×1018 cm −3 n-type doped GaAs emitters in a multilayer GaAs/Al 0.13 Ga 0.87 As heterostructure is presented. The detection mechanism is based on free carrier absorption with a broad response extending to ∼5.26 THz (57 μm), corresponding to an effective workfunction of ∼21.8 meV, which is much smaller than the offset expected for an Al fraction of x = 0.13 at a 1 × 10 18 cm −3 doping. This is attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…While the resulting systems may have collective magnetic property, the magnetism is often not uniform over the entire materials due to dopant inhomogeneity. More importantly, the dopants in a multilayer device structure have been found to migrate from the host layer to the adjacent layers during operation of the device . The elusive nature of dopants has therefore made practical implementation difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the resulting systems may have collective magnetic property, the magnetism is often not uniform over the entire materials due to dopant inhomogeneity. More importantly, the dopants in a multilayer device structure have been found to migrate from the host layer to the adjacent layers during operation of the device . The elusive nature of dopants has therefore made practical implementation difficult.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the dopants in a multilayer device structure have been found to migrate from the host layer to the adjacent layers during operation of the device. 10 The elusive nature of dopants has therefore made practical implementation difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These challenges include the low solubility limit of transition metal ion dopants, their tendency to form clusters and to occupy sites other than the cation-substitutional ones, 5 and the likelihood of dopant migration in a multilayer device structure. 6 More importantly, studies employing X-ray magnetic circular dichroism have revealed that dopants (Co, Mn, and Cr) with unpaired d electrons are in fact not the origin of ferromagnetism. Instead, it is the dopant-induced oxygen vacancy defects that contribute to ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…The heterojunction interfacial-workfunction internal photoemission ͑HEIWIP͒ detector 1,2 is a specific type of device that has been developed, which consists of several highly doped emitter and undoped barrier layers placed between highly doped contacts. Recent results from n-type HEIWIP structures show sensitivities at wavelengths up to 93 m. 3,4 The basic model 5 for the response of HEIWIP detectors consists of three mechanisms; absorption, internal photoemission, and collection of the photocarriers. While significant progress has been achieved 6 in optimizing the modeling of the absorption, there are few studies on the other two factors.…”
mentioning
confidence: 99%